PERSONAL INCOME TAX REFORMS IN SLOVENIA AND OTHER EUROPEAN ECONOMIES - Jagric, Vita; Strašek, Sebastjan; Jagric, Timotej (Journal of European Economy, 2017)
The paper examines some measures introduced in the tax system reform in Slovenia, as an example of a new EU member state. In the analysis we focus on the personal income tax. We analyze recent data for Slovenia and selected EU member states. In this context, we also discuss the question of flat tax rate suitability. Based on the presented simulation, we can conclude that the tax burden wasn’t diminished significantly. We believe that additional reforms are needed.